PERSEPSI PESERTA DIDIK TERHADAP PELAKSANAAN GERAKAN LITERASI SEKOLAH (GLS) DI SDN OMAL SAPA KECAMATAN POTO TANO - Andy Saputra; R Ramlafatma (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to describe, analyze, and evaluate the implementation of the School Literacy Movement (SLM) and to measure its effectiveness in enhancing students’ reading interest at SD Negeri Omal Sapa. The background of this study is based on the 2024 Education Report, which indicated that students’ literacy skills were below the minimum competency, necessitating systematic intervention by the school. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. Observations were conducted on the SLM program implementation, in-depth interviews were held with the principal, teachers, and several students, and documentation studies were conducted regarding school literacy policies. The research subjects included all school stakeholders involved in the implementation of SLM. The findings revealed that the SLM at SD Negeri Omal Sapa was effectively implemented through two main stages: the habituation stage and the development stage. The habituation stage focused on routine activities that foster reading habits, while the development stage emphasized improving literacy skills through more structured reading activities. The study concluded that consistent and structured implementation of SLM significantly enhances students’ reading interest, as evidenced by changes in attitudes and increased enthusiasm for literacy activities. To strengthen the program, it is recommended that the school provide a more diverse and relevant selection of reading materials to sustain and further improve students’ reading motivation.